Design and fabrication of ceiling fan cleaner / Muhamad Arif Hakimi Mohd Fadzil - Mohd Fadzil, Muhamad Arif Hakimi (2023)
In this study, a ceiling fan cleaner will be designed and fabricated to ease the cleaning work of fans at either commercial buildings, industrial buildings, or houses. It is because the design of this product is designed to be user friendly. It is also easy to handle and there is no need to clean the dust that falls from the fan. This is because there is dust container at the cleaner. So, the dust that has been wiped will fall straight to the container. Thus, there is no need to clean up the mess after the fan cleaning work. In addition, the students who are staying either in the hostel or renting any house outside the campus can also use this product to make their cleaning work easier in their stay place. Thus, they do not need to worry about cleaning the ceiling fan. The purpose of ceiling fan cleaner also can be extended to a certain length by using power screw mechanism. It is to overcome the risk of falling from ladder when they want to clean the ceiling fan by using the default way for example by using cloth, sponge, or normal ceiling fan wiper. Finally, this project is expected to reduce the work and time for the ceiling fan cleaning process. This project can also reduce the amount of work that needs to be done. The user will not need to do multiple work to complete the ceiling fan cleaning process. The user will not need to climb high stepladder that can risk the user of falling to the ground. Moreover, cleaning and collecting dust task can be combined to one work only.